a2 = - 7 , a5 = 56
nth term in GP:
an = a1 ∙ r ⁿ⁻¹
where:
a1 = first term , r = common ratio
a2 = a1 ∙ r ²⁻¹ = r¹ = a1 ∙ r
a5 = a1 ∙ r ⁵⁻¹ = a1 ∙ r ⁴
a5 = a1 ∙ r ∙ r ³
a5 = a2 ∙ r ³
56 = ( - 7 ) ∙ r ³
Divide both sides by - 7
56 / ( - 7 ) = r ³
- 8 = r ³
r ³ = - 8
r = ∛ - 8
r = - 2
a2 = a1 ∙ r
- 7 = a1 ∙ ( - 2 )
Divide both sides by - 2
- 7 / - 2 = a1 ∙ ( - 2 ) / - 2
7 / 2 = a1
a1 = 7 / 2
The sum of the n terms in GP:
Sn = a1 ∙ ( 1 - rⁿ ) / ( 1 - r )
The sum of the first five terms:
S5 = a1 ∙ ( 1 - r⁵ ) / ( 1 - r )
S5 = ( 7 / 2 ) ∙ [ 1 - ( - 2⁵ ) ] / [ 1 - ( - 2 ) ]
S5 = ( 7 / 2 ) ∙ [ 1 - ( - 32 ) ] / ( 1 + 2 )
S5 = ( 7 / 2 ) ∙ ( 1 + 32 ) / 3
S5 = ( 7 / 2 ) ∙ 33 / 3
S5 = ( 7 / 2 ) ∙ 11
S5 = 77 / 2 = 38.5
Your GP:
7 / 2 , - 7 , 14 , - 28 , 56...
The 2nd and 5th terms of a GP are -7 and 56 respectively. Find:
a. The common ratio
b. The first term
c. The sum of the first five terms
3 answers
Please what is the square for
Alphabet B
2nd term=-7
5th term=56
r=-2
Substitute -2 for r in (1)
a=-7
a=1.75
2nd term=-7
5th term=56
r=-2
Substitute -2 for r in (1)
a=-7
a=1.75